Synthesis and characterization of bovine serum albumin based nanocontainers for drug delivery appications - Topal, Elif Özlem. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2022)
Polymeric nanocontainers which consist of both a core and a polymeric mem brane have an important role for drug delivery applications. They can carry active compounds like drugs, proteins in their core and their polymeric membrane prevent the living environment from the side effects of these carried compounds. There are various types of polymeric materials that can be natural or synthetic according to their source for the production of the polymeric nanocontainers. Also, the combina tions of different polymers are used to produce highly stable nanocontainers. The main goal of this thesis study is fabrication of totally biocompatible, biodegradable, durable, nanocontainers that consist of polymeric shell and lipid core. For these reasons, conju gates made of the Bovine Serum Albumin (BSA) which is a protein and Pectin which is a polysaccharide, were synthesized through the Maillard reaction based on reduc ing sugar and proteins without using external chemicals or enzyme. The effects of protein- polysaccharide weight ratio, pH adjustment were investigated to optimize the conjugate formulation. The produced conjugates were characterized via Protein As say, SDS-PAGE and FT-IR Analysis. The polymeric nanocontainers were produced through oil-in-water miniemulsion method by using the obtained BSA and Pectin con jugates. Addition of biocompatible stabilizers had a drastic influence on the resulting features on the nanocontainers which are extensively characterized by dynamic light scattering analysis, zeta potential measurements and STEM imaging. NOTE Keywords : Biopolymeric Nanocontainer, Maillard Reaction, BSA- Pectin Conjugates.
Keywords: Polymeric drug delivery systems.; Drug delivery systems.